Assessment of barriers in lead time improvement: an exploratory study of electronics manufacturing companies in Himachal Pradesh (India). (15th December 2020) - Jamwal, Anbesh; Nayim, S.M. Towhidul Islam; Shukla, Rajendra Kumar; Agrawal, Rajeev; Gupta, Sumit
Reduction in lead time is very essential in every industry to increase the productivity, satisfy the volatile demands of a customer and sustain the market reputation among the global industries. The competition among the global industries has forced almost all industries to adopt the lean manufacturing system over the traditional manufacturing system. The present study focuses on the identification of barriers which resist the reduction of lead time in electronics industries in Himachal Pradesh. Nine critical barriers were found on the basis of data collected from the industry experts through the questionnaire survey and consultation from the different regions of Himachal Pradesh. Reduction in lead time is very important for any industry. There are always some barriers which resist the lead time reduction. Industries should know which barrier is most influencing barrier, selection of most influencing barrier can help the industries to overcome from barrier. This study investigates and ranks the barriers in lead time reduction based on the judgement of industry experts from electronics industry. Analytical hierarchy process (AHP) is used to prioritise the barriers.